2013
DOI: 10.1002/mgg3.10
|View full text |Cite
|
Sign up to set email alerts
|

A homozygous double mutation in SMN1: a complicated genetic diagnosis of SMA

Abstract: Spinal muscular atrophy (SMA), the most common autosomal recessive cause of infant death, is typically diagnosed by determination of SMN1 copy number. Approximately 3–5% of patients with SMA retain at least one copy of the SMN1 gene carrying pathogenic insertions, deletions, or point mutations. We report a patient with SMA who is homozygous for two mutations carried in cis: an 8 bp duplication (c.48_55dupGGATTCCG; p.Val19fs*24) and a point mutation (c.662C>T; p.Pro221Leu). The consanguineous parents carry the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
0
14
0
2
Order By: Relevance
“…These standards were generated from genomic DNA extracted from blood specimens, with copy numbers assessed by QCEFA (Kirwin et al., 2013). One of these reference samples (SDC1) could not be accurately accessed for SMN2 copy number using QCEFA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These standards were generated from genomic DNA extracted from blood specimens, with copy numbers assessed by QCEFA (Kirwin et al., 2013). One of these reference samples (SDC1) could not be accurately accessed for SMN2 copy number using QCEFA.…”
Section: Resultsmentioning
confidence: 99%
“…The assay conditions were first tested on SMN1 and SMN2 reference standards (n = 7) obtained from the Clinical Laboratory Improvement Amendments (CLIA)certified Molecular Diagnostics Laboratory at N/AIDHC. These standards were generated from genomic DNA extracted from blood specimens, with copy numbers assessed by QCEFA (Kirwin et al, 2013). One of these reference samples (SDC1) could not be accurately accessed for SMN2 copy number using QCEFA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One patient with typical SMA Type II showed two SMN1 copies without any intragenic mutations. Nondeleted patients with homozygous intragenic mutations have been reported in consanguineous families but it is very unlikely in a non-consanguineous family [11,12] Fig. 1 The frequency of genotypes in Cypriot SMA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although, more than 60 subtle mutations of SMN1 gene have been reported worldwide [22], homozygous subtle mutations are very rarely reported in patients with SMA. Kirwin et al reported homozygous double mutation in a SMA patient [29] and Rad et al reported homozygous point mutation (c.549delC at exon 5) which resulted in fame-shift on SMN1 gene in a SMA type I patient [30].These reports imply that although DNA sequencing is routinely carried out on SMA patient with only one copy of SMN1 gene, it should also be carried out in patients with clinical diagnosis of SMA who show even two copies of SMN1 gene [31].…”
Section: Mutation Spectrum Of Smn1 Genementioning
confidence: 99%